Comparative approach of Darcy–Forchheimer flow on water based hybrid nanofluid (Cu-Al2O3) and mono nanofluid (Cu) over a stretched surface with injection/suction - R. Sindhu; S. Eswaramoorthi; K. Loganathan; Reema Jain (Partial Differential Equations in Applied Mathematics, 2024)
The hybrid nanofluids are crucial for enhancing heat transfer efficiency in different technological and industrial operations like nuclear reactor cooling, fuel cells, drug delivery systems, etc. Taking this factor into account, the current investigation focused on the MHD Darcy–Forchheimer flow of water-based hybrid nanofluid (Cu-Al2O3) and mono nanofluid (Cu) past a stretched surface with injection/suction. Additionally, the investigation focuses on analyzing the consequences of nonlinear thermal radiation and heat consumption/generation. The governing higher-order PDEs are rehabilitated into ODEs through a suitable transformation process. Finally, we solve these equations using the quantitative approach of the Bvp4c algorithm in MATLAB and visualize the results in tables and graphs. Our study revealed that the intensified magnetic field, porosity, and injection/suction parameters suppress the fluid velocity. The fluid heat is enhanced when intensifying the radiation, and nanoparticles volume fraction parameters. Augmenting the magnetic field parameter results in a reduction in the skin friction coefficient. It is also found that the highest dwindling percentage of the skin friction coefficient is 24% (HNF), 33.38% (NF), and 25.70% (VF) when the magnetic field parameter changes from 0 to 1. The largest growing percentage of the local Nusselt number is 34.02% (HNF), 36.75% (NF) and 39.52 (VF), which occurs when the suction/injection parameter is modified from −0.3 to 0.